Overview on Topical 5-ALA Photodynamic Therapy Use for Non Melanoma Skin Cancers. (26th March 2014) - Cantisani, Carmen; Paolino, Giovanni; Faina, Valentina; Frascani, Federica; Cantoresi, Franca; Bianchini, Daniela; Fazia, Gilda; Calvieri, Stefano
Abstract : Ultraviolet radiation (UV) contributes to a variety of skin diseases including inflammation, degenerative aging, and cancer. Historically, humans have been exposed to UV radiation mainly through occupational exposure; recreational UV exposure, however, has increased dramatically in recent years, because of outdoor leisure activities and to purposely tan for cosmetic purposes. Both UVB and UVA radiation have been shown to cause DNA damage and immunosuppression, the important forms of biological damage that lead to NMSC. Nonmelanoma skin cancer (NMSC) is the most common malignancy, whose public health significance is often unrecognized which continues to grow at an alarming rate, becoming an occupational disease. Available treatments alternative to surgery include photodynamic therapy, electrochemotherapy, cryotherapy, ablative lasers, 5-fluorouracil, imiquimod, ingenol mebutate, and diclofenac. Among these, photodynamic therapy is a noninvasive technique with excellent cosmetic outcome and good curative results, when used in initial stages of skin cancers for superficial lesions. It is administered under numerous and significantly varied regimens and there are a wide range of cure rates reported, permitting treatment of large and multiple lesions with excellent cosmetic results. This is an overview of photodynamic applications especially for the treatment of NMSC, with a short focus on daylight modality.